Effectiveness and Clinical Usefulness of Electronic Agenda-setting in Psychiatric Practices: A South Texas Psychiatric PBRN Study. Issue 1 (5th January 2023) - Deuter, Melissa; Martinez, Cervando; Preikschat, Bailey; Daniels, Jennifer; Machuca, Alejandro; Martinez, Melissa; King, Van; Ticknor, Christopher; Tierney, John; Roybal, Donna
Abstract : There is a general consensus that the doctor-patient interview should be as productive and efficient as possible. This is becoming increasingly difficult in a health care insurance system that demands shorter appointment times. Clinicians must therefore find ways to condense the clinical encounter without sacrificing quality. The purposes of this study were: (1) to facilitate shared decision-making between psychiatrist and patient via pre-visit patient agenda-setting, (2) to evaluate the effectiveness and ease of use of the agenda-setting tool, and (3) to determine patient and clinician satisfaction with the clinical encounter. Patients completed questionnaires to assist in agenda-setting via an electronic tablet while in the waiting area before seeing the psychiatrist. Both patients and psychiatrists then completed post-visit questionnaires to assess their satisfaction with the encounter. We measured patient satisfaction and the extent to which the psychiatrist addressed concerns before and after the visit, as well as ease of use for the patient, psychiatrist satisfaction, and clinical helpfulness to the treating psychiatrist. Additional analyses also indicated that there was a significant increase in patient satisfaction scores, compared with an average of all previous visits, and a significant increase in the number of concerns addressed during the current visit when compared with the average number of previous concerns addressed. Patients reported little difficulty using the tablet. Similarly, psychiatrists reported that the device was helpful in the clinical setting and they expressed high levels of satisfaction with the visit. We hope our work will encourage others to use this agenda-setting tool in their practices to facilitate better patient care.